Parenting children with ADHD : 10 lessons that medicine cannot teach - Monastra, Vincent J. (Washington, D.C. : American Psychological Association, 2014)
In this second edition, Dr. Vince Monastra provides practical, step-by-step guidance to parents looking for ways to bring out the best in kids with attention-deficit/hyperactivity disorder. He presents updated lessons about the causes of ADHD, how medications work, and the problems that sleep deficits, poor nutrition, and other medical disorders can cause. He also shares his innovative approach for improving organization, task completion, problem solving, and emotional control.
Everybody doesn't have a little bit of ADHD -- Parenting doesn't cause ADHD, genes do! -- Medicines don't cure ADHD, but they can help -- Nutrition does matter -- Students with ADHD are entitled to help at school -- Kids need a reason to learn -- You'll get lost without a lesson plan -- Temperament may be inherited, but emotional control is learned -- Yelling rarely solves anything -- Now that I have their attention, what do you really want them to learn? -- Parents are people too! -- It don't come easy: troubleshooting tips -- Final thoughts: a personal perspective.
In Process-PDAL
Includes bibliographical references and index.
Keywords: Attention-deficit hyperactivity disorder -- Treatment; Problem children -- Behavior modification; Parenting; Attention-deficit hyperactivity disorder -- Treatment; Parenting; Problem children -- Behavior modification